PERSAINGAN PADA PASAR UMKM DI LINGKUNGAN SEKOLAH - Nadila Catur Sulistyo Rini; Artika Mirayanti, Della Nurcahyani, Karolina Putri, Ryan Febriansyah Hertanto, Dian Sudiantini (CV. Adiba Aisha Amira, 2024)
The development of market/traditional snacks in school canteens is increasingly crowded and competitive, especially MSMEs that need to move quickly to attract consumers. Public consumption of packaged food and drinks is increasing, especially for school children. The purpose of this research is to find out why school MI/MTS Tarbiyatul Falah children prefer to spend their money on one of the MSME actors in the canteen.